2004
DOI: 10.3168/jds.s0022-0302(04)70023-5
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Holstein Dairy Heifers after Synchronization of Ovulation and Timed AI or AI after Removed Tail Chalk

Abstract: Nonlactating Holstein dairy heifers (n=352) 13 mo of age were managed using a 42-d artificial insemination (AI) breeding period in which they received AI after removed tail chalk evaluated once daily. At AI breeding period onset (d 0), heifers were randomly assigned to receive synchronization of ovulation (100 microg of GnRH, d 0; 25 mg of PGF2alpha, d 6; 100 microg of GnRH, d 8) and timed AI (TAI; d 8) and AI after removed tail chalk for the entire AI breeding period (GPG; n=175), or AI after removed tail cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
1
16

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 34 publications
7
37
1
16
Order By: Relevance
“…Studies using Ovsynch TAI in heifers have reported that a high proportion (18 to 24%) come into estrus before the day of timed insemination (Rivera et al 2004(Rivera et al , 2005. Although our study found a similar proportion of heifers that came into estrus before scheduled timed breeding as other studies, our PR were far superior compared with these studies and others (Pursley et al 1997a), and are similar to those achieved with breeding at natural estrus (Pursley et al 1997a).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Studies using Ovsynch TAI in heifers have reported that a high proportion (18 to 24%) come into estrus before the day of timed insemination (Rivera et al 2004(Rivera et al , 2005. Although our study found a similar proportion of heifers that came into estrus before scheduled timed breeding as other studies, our PR were far superior compared with these studies and others (Pursley et al 1997a), and are similar to those achieved with breeding at natural estrus (Pursley et al 1997a).…”
Section: Discussionsupporting
confidence: 75%
“…Although our study found a similar proportion of heifers that came into estrus before scheduled timed breeding as other studies, our PR were far superior compared with these studies and others (Pursley et al 1997a), and are similar to those achieved with breeding at natural estrus (Pursley et al 1997a). Other studies using Ovsynch TAI observed PR that were 20 to 40% less than that of heifers receiving AI to a natural estrus (Pursley et al 1997a;Rivera et al 2004). The establishment, maintenance of pregnancy, and embryo growth are related to the ability of the CL to secrete P 4 (Schmitt et al 1996).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Progesterone concentrations below 1.0 ng/ml were considered low and indicative of the absence of CL, while progesterone concentrations of 1.0 ng/ml or higher were considered as an indicative of functional CL and were referred as high (Cordoba and Fricke, 2002;Rivera et al, 2004;Yusuf et al, 2010). Cows showed high progesterone concentrations on day-7 were considered to have positive response to GnRH treatment, and cows showed high progesterone concentrations on day-7 and low on day-10 were considered to have positive response to GnRH and PGF2α treatments.…”
Section: Hormone Assay and Case Definitionmentioning
confidence: 99%
“…However, these TAI protocols have not been utilized in heifers due to impaired pregnancy rate compared with AI at detected estrus [8,14]. One of the major reasons in heifers that estrus was observed before TAI and thus it failed in fertile inseminations [8,16,17]. This may occur due to early maturation of follicles compared with lactating cows [13] and results in premature estrus or ovulation [4,9,18,19].…”
mentioning
confidence: 99%